1990
DOI: 10.1557/proc-213-703
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Creep Behavior of Ordered Orthorhombic Ti2A1Nb-Based Alloys

Abstract: Titanium aluminide alloys with compositions near Ti-25A1-25Nb at.% were prepared by both rapid solidification and ingot techniques. Their tensile and creep properties were studied after heat treatment to produce various microstructures containing ordered orthorhombic (O) [1], ordered beta (βo), and α2 phases. It was found that these alloys had higher specific strength from room temperature to 760°C than conventional α2 alloys. Ductility and tensile strength of O+βo alloys were strongly dependent upon heat trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…In this poorer f values. In the case of Ti-12Al-38Nb, O platelets case, the YS value (1294 MPa) taken from a previous study provided significant strengthening for the ␤-dominated of Ti-22Al-27Nb [1] was used. microstructures, with an associated reduction in f .…”
Section: B Elevated-temperature Properties (A)mentioning
confidence: 99%
See 3 more Smart Citations
“…In this poorer f values. In the case of Ti-12Al-38Nb, O platelets case, the YS value (1294 MPa) taken from a previous study provided significant strengthening for the ␤-dominated of Ti-22Al-27Nb [1] was used. microstructures, with an associated reduction in f .…”
Section: B Elevated-temperature Properties (A)mentioning
confidence: 99%
“…pct) O-based and Ti-27Al-10Nb (at. pct)* ␣ 2 -based alloys and reported that all alloy, [1] the reported ultimate tensile strength (UTS) was as high as 1415 MPa, with f ϭ 3.6 pct (Table I). Other studies *All alloy compositions are given in atomic percent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have focused on constructing microstructure-creep relationships and determining creep deformation mechanisms [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and constructing microstructure-tensile relationships of two-phase O + bcc Ti-Al-Nb alloys. [6,8,16,[18][19][20][21][22][23]25,[27][28][29][30][31][32][33] To some extent, the tensile and creep properties of fully-O microstructures and the tensile properties of fully-bcc microstructures have been characterized.…”
Section: Introductionmentioning
confidence: 99%